Fixação de teses pelos Tribunais Superiores e seu impacto nos direitos do contribuinte - Assunção, Ana Cristina de Paulo (2023)
The main objective of this study is to reflect on the standardization of jurisprudence and the impact of thesis established on taxpayers' rights in the actions of the Executive, Judiciary and Legislative Powers. The introductory part presents the primary sources of law, that is, the principles and rules that regulate the relationship between the tax authorities and the taxpayer which are the basis for the judgments of the Superior Courts and for the formation of precedents. The second part deals with the inclusion of precedents as a source of law based on the comparative analysis of the civil law system and the experiences of the common law. In the third part, it is proposed to describe the legislative evolution of the system of precedents and present the concepts that compose it. Then, based on analysis of practical cases, a classification of precedents is proposed in six categories correlated with the impact of their application on the taxpayer's rights. Afterwards, the reflections of the application of precedents to the taxpayer's rights are identified in activities of enrollment, debt registration, acts of tax audit and judgments in both administrative and judicial Courts, including, in what is correlated to the prospective effects and use of distinguishing technique. Finally, it describes the impact of precedents within the scope of the Legislative Power. The reader, supported by the propositions presented, is invited to reflect on the precedents as a procedural instrument to guarantee the taxpayer´s rights and the impacts arising from its practical application during these eight years of the New Code of Civil Procedure (NCPC)